Shading-based high-quality 3D object reconstruction - Xu, Di (2016)
3D object reconstruction is the process of reconstructing real objects into the digital world. Reconstructing the shape of a 3D object from multi-view images under unknown, general illumination is a fundamental problem in computer vision. Extensive research has been done in this area and many techniques have been developed. Though the state-of-the-art has achieved great success, many methods still have various underlying requirements or heavy assumptions that limit their application scope in practice. This thesis investigates both the shape refinement and its related lighting recovery. We approach the problem with different focuses: quality, robustness and efficiency. Our goal is to design and develop effective algorithms that solve the long-lasting problems in 3D reconstruction.